The importance of neighborhood ecological assets in community dwelling old people aging outcomes: A study in Northern Portugal - Bastos, Alice M.; Faria, Carla G.; Moreira, Emília; Morais, Diana; Melo-de-Carvalho, José M.; Paul, M. Constança (Frontiers in Aging Neuroscience, 2015)
Human development is a bidirectional, person-context relational process, but scarce evidence is available about the relation between the individual variability across the life-span and the neighborhood ecological assets. Therefore, it is important that research focus not only on personal characteristics but on ecological assets as well. This way this study aims to analyze the association between neighborhood ecological assets categorized into 4 dimensions: human, physical or institutional, social or collective activity, accessibility, and the individual functioning. A 3% sample of residents aged 65 years and older in 2 downtown and 3 uptown parishes stratified by age and sex was interviewed at home using a protocol that included the Portuguese version of the Barthel Index in basic activities of daily living (BADL), the Lawton Instrumental Activities of Daily Living Scale (IADL), the Mini Mental State Examination (MMSE) and the Geriatric Depression Scale-15 items (GDS) for evaluating functionality, cognitive performance and depression. The 162 participants were aged on average 75y (sd=7.0), 54% were women and 90% had less than 7 years of education. The majority of participants were independent in BADL (M=90; sd=17.7) and moderately dependent in IADL (M=13, sd=6.0), 20% showed cognitive impairment and a mean score of 8 (sd=2.1) in GDS-15. After controlling for the effect of socio-demographic characteristics, functionality and cognitive performance decreases in persons with worst outdoor mobility. On the other hand depressive symptoms are less common as the number of recreation opportunities, namely associative groups (cultural, educative, professional), increases. These results suggest that aging policies and practices must be ecologically embedded.